Effect of Perioperative Instructions on Postoperative Discomforts and Satisfaction Level among Patients Undergoing Thyroidectomy - Yasmin F. M. Abd Elazeem; Nesrine E. M. Abdel-Karim; Eman F. A. M. Aly (Evidence-Based Nursing Research)
Context: Thyroidectomy is a type of surgery directed to remove all or part of the thyroid gland. Documented complications after thyroidectomy are rare, but their consequences can often be life-threatening. Patients who receive perioperative instructions about what to expect after the operation often have better coping with postoperative discomforts minimizes post-surgical complications and reduces the duration of hospitalization. It also improves patient safety and reduces the anxiety induced by the intervention. In addition to this, it elevates the patient's satisfaction level. So, perioperative instructions are essential.